Clinically Significant Outcome Improvement After Hip Arthroscopy in Patients With Femoroacetabular Impingement Syndrome and Severe Femoral Torsion. Issue 10 (6th October 2021) - DeFroda, Steven F.; Alter, Thomas D.; Bodendorfer, Blake M.; Newhouse, Alexander C.; Bessa, Felipe S.; Williams, Joel C.; Nho, Shane J.
Background: The influence of femoral torsion on clinically significant outcome improvement after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) has not been well-studied. Purpose: To quantify femoral torsion in FAIS patients using magnetic resonance imaging (MRI) and explore the relationship between femoral torsion and clinically significant outcome improvement after hip arthroscopy. Study Design: Cohort study; Level of evidence, 3. Methods: Included were patients who underwent hip arthroscopy for FAIS between January 2012 and August 2018 and had 2-year follow-up and preoperative MRI scans containing transcondylar slices of the knee. Participants were categorized as having severe retrotorsion (SR; <0°), normal torsion (NT; 0°-25°), and severe antetorsion (SA; >25°) as measured on MRI. Patient-reported outcomes (PROs) included the Hip Outcome Score–Activities of Daily Living, Hip Outcome Score–Sports Subscale, modified Harris Hip Score, 12-item International Hip Outcome Tool (iHOT-12), and visual analog scale (VAS) for pain and satisfaction. Achievement of Patient Acceptable Symptom State (PASS) and substantial clinical benefit (SCB) were analyzed among cohorts. Results: Included were 183 patients (SR, n = 13; NT, n = 154; SA, n = 16) with a mean age, body mass index, and femoral torsion of 30.6 ± 12.1 years, 24.0 ± 4.4 kg/m 2, and 12.55° ± 9.58°, respectively. The mean torsion was –4.5° ± 2.6° for the SR, 12.1° ± 6.8° for the NT, and 31.0° ± 3.6° for the SA group. There were between-group differences in the proportion of patients who achieved PASS and SCB on the iHOT-12, pain VAS, and any PRO ( P < .05). Post hoc analysis indicated that the SA group achieved lower rates of PASS and SCB on the iHOT-12 and pain VAS, and lower rates of PASS on any PRO versus the SR group ( P < .05); the SR group achieved higher rates of PASS and SCB on pain VAS scores versus the NT group ( P = .003). Conclusion: The orientation and severity of femoral torsion during hip arthroscopy influenced the propensity for clinically significant outcome improvement. Specifically, patients with femoral retrotorsion and femoral antetorsion had higher and lower rates of clinically significant outcome improvement, respectively.